Ứng dụng paclitaxel PM - carboplatin trong điều trị ung thư phổi không tế bào nhỏ giai đoạn tiến xa - Thanh, Trần Đình; Dũng, Nguyễn Huy; Trâm, Võ Trần Ái; Nhân, Nguyễn Thiện; Toàn, Đinh Trọng; Hà, Chu Thị (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.